Luminescent Lanthanide Labels - J. Charbonniere, Loic (Current Inorganic Chemistry (Discontinued), 2011)
This chapter describes the properties of luminescent lanthanide complexes that can be used in biological solutions for luminescence based labelling applications. The particular photo-physical specifications of this family of luminescent labels will be described, followed by the chemical and physico-chemical requirements necessary to reach high luminescence and good labelling activity. Following these criteria, examples of the literature will be detailed, following a classification based on the chemically activated function used in the labelling process.
Keywords: fluoro-immunoassays